A state of the art review of " verification the shear reinforcement distribution across the web of "reinforced concrete deep beams (Eurasian Journal of Engineering and Technology, 2023)
As transfer girders in bridges and high buildings, RC deep beams are important structural systems carrying enormous loads over small spans that must be safe. The shear strength of deep beams is not reliably and properly predicted by recent design standards in practice codes, and in some situations, they are dangerous. To improve current design methodologies and more precisely anticipate the shear capacity of such members, it is the goal of this effort to understand the behavior of deep beams and their controlling factors. This study examines the impact of vertical reinforcement and shear span ratios on failure modes and strengths. This study summarizes earlier research on strengthening deep beams by perpendicular reinforcement ratio and adding SFRC technology. It also illustrates the impact of several strengthening materials (NSC, HSC, and RPC) on the flexural strength of RC beams.